2018
DOI: 10.1002/slct.201703033
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Silane‐Reduction of Carboxylic Esters and Lactones: Selective Synthetic Methods to Aldehydes, Lactols, and Ethers via Silyl Acetal Intermediates

Abstract: Practical procedures for the production of aldehydes, lactols, and ethers are offered by the palladium‐catalyzed silane‐reduction of carboxylic esters and lactones. The partial reduction of carboxylic esters or lactones with 1,1,3,3‐tetramethyldisiloxane in the presence of commercially available palladium on carbon (Pd/C) and some copper compounds as a co‐catalyst smoothly proceeds under mild conditions to afford the silyl acetal derivatives in high yields, which are easily converted to the corresponding aldeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Analogously to the mechanism proposed in Scheme 2 for carbonyl compounds as alkylating agents, the hemiacetal can afford the desired ether through a second reduction, by either direct hydrogenolysis or via oxocarbenium cation and/or enol ether intermediates (Scheme 16a) [121,122] . This pathway is commonly designed in carboxylic acid derivatives chemistry as a C−OX cleavage pathway, in clear contrast with a C−OR cleavage pathway in which the hemiacetal is in equilibrium with an aldehyde plus an alcohol [23,26,29,121f] . In addition, the same aldehyde/alcohol mixture of products can be formed by the direct reduction of the carboxylic acid derivative employed as alkylating agent.…”
Section: Reductive Etherification Of Alcohols With Carboxylic Acid Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogously to the mechanism proposed in Scheme 2 for carbonyl compounds as alkylating agents, the hemiacetal can afford the desired ether through a second reduction, by either direct hydrogenolysis or via oxocarbenium cation and/or enol ether intermediates (Scheme 16a) [121,122] . This pathway is commonly designed in carboxylic acid derivatives chemistry as a C−OX cleavage pathway, in clear contrast with a C−OR cleavage pathway in which the hemiacetal is in equilibrium with an aldehyde plus an alcohol [23,26,29,121f] . In addition, the same aldehyde/alcohol mixture of products can be formed by the direct reduction of the carboxylic acid derivative employed as alkylating agent.…”
Section: Reductive Etherification Of Alcohols With Carboxylic Acid Derivativesmentioning
confidence: 99%
“…More recently, in 2018, Motoyama and co‐workers showed that a system based on the combination of Pd/C and Cu(acac) 2 was able to reduce lactones to silyl acetals employing TMDS as reducing agent (Scheme 20G) [121f] . The silyl acetal intermediates were further transformed into the corresponding ethers by the addition of TMS−OTf in catalytic amounts at −78 °C.…”
Section: Reductive Etherification Of Alcohols With Carboxylic Acid Derivativesmentioning
confidence: 99%
“…2,3 In synthetic chemistry, they promote highly efficient and selective reactions such as the functionalization of inactivated C-H bonds in catalytic processes 4 or the reduction of carbonyl-containing molecules. [5][6][7][8] Recent studies have highlighted new utilizations for hydrosilanes to recover valuable molecules through C-O bond reduction/cleavage of oxygenated feedstock such as CO2, 9 wood lignin 10 and plastics 11 toward a circular economy with low oil dependency. Currently, hydrosilane synthetic strategies rely on energy-intensive processes which involve strong reducing agents such as LiAlH4.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported the catalytic silanereduction of carbonyl compounds using commercially available palladium on carbon (Pd/C) as a catalyst. [9] During the course of these studies, we became aware of the gas evolution and formation of silyl esters and isobutene as a by-product in the Pd-catalyzed reaction of tert-butyl esters with hydrosilanes. [10] Similar to the triruthenium cluster system, the present Pd-hydrosilane system also initiates the ring-opening oligomerization of THF [7] (details see, Supporting Information).…”
mentioning
confidence: 99%
“…Selective conversion of tert-butyl ethyl succinate(8) to monoethyl succinate(9). Conditions: a) PdCl 2 /TMDS/ DME/40 8C; b) NaOH/MeOH/25 8C Esterification or transesterification of 5 a and 1 a.…”
mentioning
confidence: 99%